Civil engineering construction contracts - O'Reilly, M. P. (Thomas Telford, 1999)
This book provides a solid background on various principal civil engineering contracts including the ICE 6th, the NEC2, the Arbitration and Conciliation Acts and the Housing Grants, Construction and Regeneration Act 1998. It also includes commentary on the ICE 7th and international contracts.